SUB THALAMIC NUCLEUS DEEP BRAIN STIMULATION: IRAQI CASE SERIES (Iraqi Journal of Medical Sciences, 2016)
Background:Sub thalamic nucleus (STN) Deep brain stimulation (DBS) electrodes are implanted into STN and programmed by external pulse generator. DBS alleviates the cardinal Parkinson disease symptoms and reduce the need for levodopa and related drugs and eventually reduces levodopa-related motor complications in advanced Parkinson's disease.Objective:To evaluate the STN DBS implantation in Parkinson disease patients.Methods:A retrospective evaluation of data base of the patients operated on for STN DBS between Jan. 2010 and Jan. 2011. The study involved 11 patients (10 males and 1 female) with an age range between 39 and 65. Surgical implantation was done in the Neurosciences Hospital in Baghdad. Unified Parkinson's disease Rating Scale was reported before surgery and 3 monthly after implantation. Paired t test was used to test the significance of difference between 2 means.Results:Highly significant differences (P < 0.0001) in the activities of daily living, Tremor, Rigidity, Bradykinesia and Gait parameter. There was no difference in Postural stability before and after. There was 65% of the patients reduced their levodopa medication dosage after STN DBS. One patient out of 11 (9%) developed intracerebral hemorrhage. Conclusions: STN DBS is very successful in managing motor clinical manifestations in advanced Parkinson disease and reducing levodopa medication. Key worlds:Parkinson, Deep brain stimulation, subthalamic
Keywords: Parkinson; Deep brain stimulation; subthalamic